Comparative study of duraplasty and non duraplasty in Chiari 1 malformation with syringomyleia our institute experience - Naik, B. D. Bharath Singh Naik Singh; Prasad, Kadali Satyavara; Sandeep, B.; Satyanarayana, S. (International Journal of Research in Medical Sciences, 2017)
Background: The prevalence of chiari malformation, defined as tonsillar herniations of 3 to 5 mm or greater, is estimated to be in the range of one per 1000 to one per 5000 individuals. The objective was to study the clinical presentation and outcome of ACM syrinx after foramen magnum decompression, c1 posterior arch removal duraplasty and without duraplasty. Methods: The study included 75 cases admitted with ACM with syrinx in neurosurgery ward in King George hospital, Visakhapatnam, Andhra Pradesh, India, during a period of five years. Results: Clinical improvement correlated strongly with enlargement of the subarachnoid cisterns and also correlated with reduction in size of the syrinx cavities. Postoperatively all the patients had decreased neck pain and two third of the patients had improvement in nystagmus, headache and dissociative anaesthesia in few cases. Conclusions: In the available literature, the treatment options offered for ACM syrinx are foramen magnum decompression and c1posterior arch removal, release of compression bands, which were followed in our institute also. We have compared pre-and post of MRI. Clinical improvement has been observed in 2 thirds of patient after a period of 2 year period follow up.